The Somme - Farrar-Hockley, Anthony 1924-2006 (Fortunes of war (Bristol, England), 2004)
At 7:30am on July 1st, 1916, fourteen British divisions climbed out of their trenches along an eighteen-mile front north of the Somme and marched slowly forward, each man carrying sixty-six pounds of kit, in wave after wave of extended lines, steadily on towards the German defenses. They expected to find the enemy barbed wire, trench systems, artillery and defenders all annihilated by the week-long preliminary bombardment by 1,350 guns. Instead they were massacred by German artillery and machine guns, first as they plodded across no-man's-land and then as they bunched to struggle through such gaps as existed in the often uncut barbed wire. By the end of the day no fewer than 57,000 men had fallen, 19,000 of them killed, and without gaining a lodgment in the German defenses, except on the right of the line next to the five French divisions also taking part in the offensive. A catastrophe without parallel in British history, this first day on the Somme still continues to provoke ferocious indictments of Sir Douglas Haig and his subordinates. Undoubtedly they committed errors of judgment tragic in their consequences, even if the errors are more easily perceived with hindsight. But the causes of the catastrophe are to be found as much in circumstance as in the mistakes of the British high command.